The Relationship of Sleep quality and Cognitive Failure among University Students: A Quantitative Study (Journal of Education and Educational Development, 2024)
This research investigates the risk factors of poor sleep quality on cognitive performance among university students in Karachi, Pakistan. This study employed a quantitative survey-based approach. N= 202 participants between 18 to 25 years were selected through convenient sampling technique. Sleep Quality Scale (SQS) (Yi, et. al., 2006) was administered to assess quality of sleep and Cognitive Failure Questionnaire (CFQ) developed by Broadbend et. al., 1982 was used to assess cognitive performance among the participants. The collected data was thereafter analyzed using descriptive and inferential statistics via SPSS (Version 22). Correlation and regression analysis were done to investigate the relationship and level of variance between the variables. Results revealed significant relationship between sleep quality and cognitive performance (p <.05) providing valuable insight on the importance of sleep and cognitive performance with regard to young population.